Juridical Analysis of Legal Protection for Land Deed Officials (PPAT) Undergoing Investigative Proceedings by the Supervisory and Advisory Council of PPAT - Mirza Tri Liestina; Tunggul Anshari; Endang Sri Kawuryan (INTERNATIONAL JOURNAL ON LANGUAGE, RESEARCH AND EDUCATION STUDIES, 2026)
Land Deed Officials (Pejabat Pembuat Akta Tanah or PPAT) play a central role in the Indonesian land law system because they are authorized to issue authentic deeds concerning land rights transactions. In practice, deeds made by PPAT may become disputed or linked to alleged criminal offences, placing PPAT in the investigation process. This study examines the legal protection available to PPAT during investigations and analyses the position and limits of the Supervisory and Guidance Council for PPAT within that framework. Using a normative juridical method with statutory and case approaches, this study analyses primary and secondary legal materials through grammatical and systematic interpretation. The findings show that legal protection for PPAT has been recognized through supervision, guidance, and legal assistance. However, the current regulatory framework does not yet provide clear procedures on the summons of PPAT, the limits of professional confidentiality, the use of deeds and official documents in investigations, and the forms of institutional assistance available. The Supervisory and Guidance Council for PPAT therefore remains important in institutional supervision, but has not been clearly formulated as a procedural control mechanism in the investigation stage. Stronger regulation is needed to ensure greater legal certainty and a more balanced relationship between investigative authority, official duties, and legal protection for PPAT.